2015
DOI: 10.3390/biology4020298
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Enrichment Reverses Histone Methylation Changes in the Aged Hippocampus and Restores Age-Related Memory Deficits

Abstract: A decline in long-term memory (LTM) formation is a common feature of the normal aging process, which corresponds with abnormal expression of memory-related genes in the aged hippocampus. Epigenetic modulation of chromatin structure is required for proper transcriptional control of genes, such as the brain-derived neurotrophic factor (Bdnf) and Zif268 in the hippocampus during the consolidation of new memories. Recently, the view has emerged that aberrant transcriptional regulation of memory-related genes may b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
51
3
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(60 citation statements)
references
References 42 publications
3
51
3
3
Order By: Relevance
“…Although enrichment failed to protect learning against age-related deficit, it alleviated the deficit in short-term memory exhibited by SC aged rats. Thus, late enriched environment exposure mitigates age-related deficit, in agreement with previous studies (e.g., Kobayashi et al 2002;Harburger et al 2007;Freret et al 2012;Kumar et al 2012;Morse et al 2015;Fuchs et al 2016;but Bouet et al 2011). The present results also showed that, although EE young adults outperformed SC young adults on a measure of platform-search accuracy (annulus crossing), enrichment had no beneficial effects on the recent memory probe trial in aged subjects.…”
Section: Spatial Memory Is Impaired In Aged Rats Housed In Standard Csupporting
confidence: 92%
“…Although enrichment failed to protect learning against age-related deficit, it alleviated the deficit in short-term memory exhibited by SC aged rats. Thus, late enriched environment exposure mitigates age-related deficit, in agreement with previous studies (e.g., Kobayashi et al 2002;Harburger et al 2007;Freret et al 2012;Kumar et al 2012;Morse et al 2015;Fuchs et al 2016;but Bouet et al 2011). The present results also showed that, although EE young adults outperformed SC young adults on a measure of platform-search accuracy (annulus crossing), enrichment had no beneficial effects on the recent memory probe trial in aged subjects.…”
Section: Spatial Memory Is Impaired In Aged Rats Housed In Standard Csupporting
confidence: 92%
“…Combined with evidence for H3.3 accumulation, our data suggest that histone subunit composition of nucleosomes is altered with age, which may have broad effects on surrounding chromatin. For example, H2A.Z tends to occupy nucleosomes containing distinct H3 modifications compared to canonical H2A (Sevilla and Binda, 2014), such that age-related shifts in H2A.Z may be accompanied by shifts in other histone marks, many of which are also altered in aged mice (Peleg et al, 2010, Walker et al, 2013, Morse et al, 2015). …”
Section: Discussionmentioning
confidence: 99%
“…In the context of aging and neurodegenerative conditions, histone acetylation has been extensively studied and is unmistakably associated with facilitating learning and memory (Mai et al, 2009;Gräff et al, 2012). On the other hand, changes in histone methylation states in the brain, relative to cognitive functions, is a relatively unexplored area of research (Gupta et al, 2010;Jarome and Lubin, 2014;Morse et al, 2015). Methylation of the histone tail typically occurs at specific lysine (K) residues, such as H3K4, H3K9, H3K27, H3K36, H3K79, and H4K20, and can either activate or repress transcription (Vakoc et al, 2006).…”
Section: Introductionmentioning
confidence: 99%